INTERACTIVE STRATEGY TRAINER FOR ACTIVE READING AND THINKING (ISTART) FOR THE STUDENTS’ READING COMPREHENSION - Hasnawati Latif (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2017)
This research aims to find the improvement of the students’ reading in literal comprehension especially main idea and supporting idea in reading comprehension use of ISTART Strategy at Class VIII.5 of SMPN 2 Sungguminasa in the 2012/2013 Academic Year. The researcher used a Classroom Action Research (C.A.R). It was consisted of two cycles. In each cycle consisted of four meetings. The research subject was the students in class VIII.5; it consisted of 35 students with 18 men and 17 women. The researcher obtained the data by using reading test and observation sheet. The research findings indicates that using ISTART Strategy could improve the students’ reading comprehension, from table 1 indicated that there was improvement the students’ Main Idea from cycle I to cycle II, where as in cycle I the students’ achievement main idea in reading was 6.65, but after evaluation in cycle II the students’ main idea in reading became 7.36. The other hand the students’ supporting idea in reading was improved cycle I to cycle II, where as in cycle I the students’ supporting idea in reading was 6.78 but after evaluation in cycle II the students’ supporting idea in reading became 7.38. It means that the use ISTART Strategy could improve the students’ reading comprehension at VIII.5 Class of the second year students of SMPN 2 Sungguminasa.